Electronic and steric effects controlling monomer–dimer self-assembly in 6H-1, 4-diazepinoporphyrazines: an experimental and theoretical study. Issue 7 (25th January 2023) - Tarakanov, Pavel A.; Simakov, Anton O.; Pushkarev, Victor E.; Konev, Dmitry V.; Goncharova, Olga A.; Slesarenko, Nikita A.; Tarakanova, Ekaterina N.; Nefedov, Sergey E.; Stuzhin, Pavel A.
Abstract : The main factors governing the dimer–monomer self-assembly in 6 H -1, 4-diazepinoporphyrazines are shown. Abstract : A series of 5, 7-disubstituted 1, 4-diazepinoporphyrazinato magnesium(ii ) and nickel(ii ) complexes, including two novel compounds, were obtained by metal-templated macrocyclization. A combination of X-ray diffraction, 1 H NMR, UV-vis, and electrochemical analyses allowed us to study their tendency towards H-type dimerization and trace the influence of structural and solvation factors on dimer stability. Based on the physicochemical and theoretical DFT calculation data, it was found that the main binding forces between 6 H -1, 4-diazepinoporphyrazine decks in the dimers were efficient π–π donor–acceptor interactions induced by the interdeck C–H⋯N hydrogen bonds. Furthermore, the metal–ligand (Pz 2− → M 2+ ) electronic interactions have a key influence on the π–π stacking of the porphyrazine cores. It was shown that the displacement of the metal ion out of the macrocycle plane induced by coordinating agents can trigger the dissociation of the dimer, since the resulting enhancement of the donor–acceptor electronic interaction between the metal ion and the π-system of the ligand leads to a subsequent weakening of the π–π stacking of the porphyrazine cores. The TD-DFT calculations predicted the non-degeneracy of the HOMO−1 → LUMO and HOMO → LUMO+1 transitions in the 6 H -1, 4-diazepinoporphyrazine H -dimers, which explains the Q-band splitting in their UV-vis spectra.